Maximal oxygen consumption and oxygen muscle saturation recovery following repeated anaerobic sprint test in youth soccer players - Michailidis, Y.; Chatzimagioglou, A.; Mikikis, D.; Ispirlidis, I.; Metaxas, T. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The purpose of the study was to examine whether differences in aerobic capacity (VO2max) influence muscle reoxygenation following repeated anaerobic sprint test (RAST) in soccer players. We hypothesized that muscle reoxygenation is faster in players with higher aerobic capacity. METHODS: Ten male, youth soccer players participated in the study and performed RAST on a synthetic grass field. Oxygen saturation in muscle (StO2) of the right vastus lateralis muscle was measured by near-infrared spectroscopy. Half the time that was required for StO2 recovery (T1/2 StO2) after RAST was used to evaluate the reoxygenation in the recovery period after testing. The T1/2 StO2 was defined as the time from the end of RAST testing to the time of reaching 50% of StO2. Aerobic capacity (VO2max) was estimated by the Yo-Yo Intermittent Recovery Test level 1 (YYIR1). RESULTS: The T1/2 StO2 had a significant inverse correlation with VO2max (r=-0.71; P=0.021) and with the distance which was covered by players on YYIR1 test (r=-0.71; P=0.021). In contrast, StO2 recovery rate showed no significant correlations with the VO2max in subjects. CONCLUSIONS: These results indicate that aerobic capacity can influence vastus lateralis reoxygenation following RAST in youth soccer players.